Gestão pela qualidade total e desempenho financeiro : um estudo da geração de riqueza ao acionista em empresas vencedoras de prêmios nacionais da qualidade do continente americano - Bassan, Heder (Universidade Federal de São Carlos, 2016)
Many authors of total quality management suggest a positive relationship between the implementation of Total Quality Management and financial performance of companies. However, empirical studies have produced mixed results due to methodological limitations of data analysis and performance indicators used. In this sense, this thesis aims to analyze the shareholder value creation using value financial indicators of winning companies of national quality awards in the Americas and to compare them to companies operating in the same economic sector. The use shareholder value performance indicators and winning companies of national awards quality seven Western Hemisphere countries is a differential of this thesis in relation to other studies. The financial data was collected from the Economática system database in specialized sites on the disclosure of financial statements and own sites of the winning companies of this research study object. The time period of analysis is ten years. The hypotheses about the companies performance on creating shareholder value were tested applying MANOVA and Factorial Analysis. The results point out the quality award winning companies has created more value to their shareholders than the other companies operating on the same economic sector.
Keywords: Gestão pela qualidade total; Prêmio nacional da qualidade; Desempenho financeiro; Geração de riqueza para o acionista; Total quality management; National quality award; Financial performance; Generating wealth for shareholders; ENGENHARIAS::ENGENHARIA DE PRODUCAO